Acetoacetyl-CoA thiolase regulates the mevalonate pathway during abiotic stress adaptation - Soto, Gabriela Cynthia (2011)
Acetoacetyl-CoA thiolase (EC 2.3.1.9), also called thiolase II, condenses two molecules of acetyl-CoA to give acetoacetyl-CoA. This is the first enzymatic step in the biosynthesis of isoprenoids via mevalonate (MVA). In this work, thiolase II from alfalfa (MsAACT1) was identified and cloned. The enzymatic activity was experimentally demonstrated in planta and in heterologous systems. The condensation reaction by MsAACT1 was proved to be inhibited by CoA suggesting a negative feedback regulation of isoprenoid production. Real-time RT-PCR analysis indicated that MsAACT1 expression is highly increased in roots and leaves under cold and salinity stress. Treatment with mevastatin, a specific inhibitor of the MVA pathway, resulted in a decrease in squalene production, antioxidant activity, and the survival of stressed plants. As expected, the presence of mevastatin did not change chlorophyll and carotenoid levels, isoprenoids synthesized via the plastidial MVA-independent pathway. The addition of vitamin C suppressed the sensitive phenotype of plants challenged with mevastatin, suggesting a critical function of the MVA pathway in abiotic stress-inducible antioxidant defence. MsAACT1 over-expressing transgenic plants showed salinity tolerance comparable with empty vector transformed plants and enhanced production of squalene without altering the 3-hydroxy-3-methylglutaryl- CoA reductase (HMGR) activity in salt-stress conditions. Thus, acetoacetyl-CoA thiolase is a regulatory enzyme in isoprenoid biosynthesis involved in abiotic stress adaptation.